Blended Learning and Learning Outcomes: The Mediating Role of Student Engagement in Indonesian Secondary Education - Rufi'i Rufi'i; Dani Chandra Yudho Pranoto; Budi Nur Rahman; Sabrina Aulia Rizki; Nurudeen Olalekan Orunbon; B. B. Harianto; Rufi'i Rufi'i; Dani Chandra Yudho Pranoto; Budi Nur Rahman; Sabrina Aulia Rizki; Nurudeen Olalekan Orunbon; B. B. Harianto (Universitas Negeri Malang, 2026)
Blended learning has increasingly been adopted in secondary education as a strategic response to the demand for more effective and contemporary instructional practices; however, the mechanisms through which it influences academic achievement remain insufficiently explained. This study examines student engagement as a mediating process linking blended learning to learning outcomes, shifting the focus from technological integration toward learner-centered mechanisms. A cross-sectional quantitative design was employed using survey data from 300 secondary school students. Data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4, involving assessment of measurement reliability and validity, followed by structural model and mediation analysis with 5,000 bootstrap resamples. The results demonstrate that blended learning has a significant positive effect on student engagement and learning outcomes, while student engagement also exerts a strong positive influence on learning outcomes. Mediation analysis confirms that student engagement partially mediates the relationship between blended learning and academic performance. These findings indicate that blended learning enhances learning outcomes both directly and indirectly by fostering students’ cognitive and behavioral involvement. Overall, the study highlights student engagement as a key mechanism through which blended learning environments translate instructional design into meaningful educational gains in secondary education contexts.